Let's say we have an object falling through an accelerated field from r to s. I would say a gravitational field, as it is by the same process as gravity, but I will be applying a different constant of motion within the field.(adsbygoogle = window.adsbygoogle || []).push({});

If the constant of motion is something like (1 - b / r) = (1 - (v_r/c)^2), or (1 - b / r) / (1 - (v_r/c)^2) = K (constant for all r), where b is also constant, then the acceleration in terms of r can be found with

b / r = (v_r/c)^2, b / s = (v_s/c)^2

a = d(v^2) / (2 dr)

a = (v_s^2 - v_r^2) / (2 dr), where r - s = dr

a = c^2 (b / s - b / r) / (2 (r - s))

a = c^2 b (r - s) / (2 r s (r - s))

a = c^2 b / (2 r^2)

But what I want to know is how we would find the acceleration similarly to the above example with a constant of motion within an accelerated field of (1 - b / r) = (1 - v_r / c) / (1 + v_r / c) instead?

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Differentiating acceleration using constant of motion

Can you offer guidance or do you also need help?

Draft saved
Draft deleted

**Physics Forums | Science Articles, Homework Help, Discussion**